Spectroscopic Analysis of Selenium Nanoparticles Synthesized by Saccharomyces boulardii for the Production of Craft Beer - Lourdes González-Salitre; Luis Guillermo González-Olivares; Alexis Alejandro Salazar-Navarro; David Cervantes-García; Dagoberto Durán-Hernández; Ricardo Torres-Ramos; Mary Triny Beleño-Cabarcas; Ulin Antobelli Basilio-Cortes (Fermentation)
Selenium is an essential micronutrient which is found in many foods and beverages in low concentrations. Craft beer, one of the most widely consumed fermented beverages globally, presents a strategic opportunity for selenium intake through organic nanoparticles. This study aimed to confirm the presence of selenium nanoparticles in the fermentation process of an ale-style beer using S. boulardii yeast selenized with Na2SeO3 (74 ppm), through spectroscopic analysis and TEM. The yeast accumulated 5.92 mg/g of dry cell mass, and the beer contained 0.642 mg/g of selenium. UV-VIS detected nanoparticles with a peak at 300 nm and FT-IR at a wavelength of 1398.85 cm−1. The particle size ranged between 74 to 175 nm, with a maximum ζ-potential of −4.2 mV, an electrophoretic mobility of −0.3492 μm × cm Vs−1, and a conductivity of 2.656 mS cm−1. TEM analysis revealed that the nanoparticles exhibited circular/ovoid shapes. The fermentation process, combined with the ingredients used to produce ale-type craft beer, proved to be a feasible method for the biosynthesis of selenium nanoparticles using S. boulardii, offering a reliable option for developing and innovating functional craft beers.